ADAPTATION OF ROBOTIC MILKING OF DAIRY COWS IN NIGERIA: CONSTRAINTS AND PROSPECTS - OGUNSINA , B. S. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Milking of dairy cows was characteristically a backbreaking job which constituted great barrier to the social life of dairy farmers in the past. Having gone through different stages of development over the years, the introduction of robotic milking system (RMS) most recently brought readical changes to milk harvesting, offering great opportunities for countries with adequate potentials to expand capacity in dairy farming. This paper reports the success of robotic milking technology sequel to a visit to some dairy farms in Israel during a Mashav training. Emphasis was laid on the Lely Astronaut Milking Robot (a robotic milking system commonly used on dairy farms in Europe, United States and Israel). Considering the ever increasing worldwide demand for dairy products and the amazing prospects that RMS provides for milk harvesting in dairy farming, the Nigerian dairy industry was appraised with the view to revive it from the nauseating level to which it has deteriorated. Thou the importation of foreign high milk-yielding breeds of cow has failed in the past and Nigeria may not yet be ripe for RMS, vested policy interest is advocated, especially to uprade indigenous dairy products such as the warakasi (cheese), nono (fermented or soured skimmed milk), kindirmo (fermented whole milk) and manshanu (butter) through an integrated rural networking with the Fulani pastoralists. These local dairy products when upgraded to international standard promises to boost income obtainable from dairy farming in Nigeria.